Ethical Issues: Good, Bad, and Ugly - Roann Barris (Academic Chairpersons Conference Proceedings, 2018)
Censorship: it is unlikely that any academic, especially in the arts, would come out in favor of censorship. But what is the right course of action when a student's work in a graduation show offends the public? And if steps are taken to remove the presumably offensive work, are we betraying our beliefs about the value of student's work or promoting good relationships with the public? This has been an active year for ethical questions about art – but who expect them to be our own issues? Details about this case and all the roles played will be provided as we search for a workable solution.
Keywords: censorship; art museums and the public